Development of plug-in hybrid electric motorcycle powertrain system - Mohd Izrey Izuan, Mat Lazin (2013)
Plug-in hybrid electric vehicles are new alternatives that meet the efforts to develop more sustainable means of transportation and reduce fuel consumption. However, this trend could bring some circumstance to Powertrain systems, such as limits space packaging, weight of the Powertrain component, and the capability of plug-in in recharging the battery for Powertrain system. The PHEV design plays a significant role in sizing of the battery pack and cost. To cope with some of those problems, this thesis proposes a development of plug-in hybrid electric motorcycle Powertrain system with the parallel Powertrain system configuration in order to achieve less emission and reduce fuel consumption. A 175 cc ICE motorcycle is selected and converted into a PHEM. A brushless DC (BLDC) motor assembled into working and integrating with ICE to propel the motorcycle. The nominal powers are 13.8 kW and 5 kW for the ICE and BLDC respectively. ADVISOR as a main program to simulate the Powertrain system for PHEM and compared the Powertrain system with the conventional Modenas Jaguh 175cc. From the result the PHEM can reduce fuel consumption while less emission produced by the Powertrain system. The performance for PHEM also can compete with the conventional although the weight for the PHEM is a little bit heavier